HUBUNGAN DISIPLIN DALAM PEMBELAJARAN PRAKTIK DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MENGOLAH MAKANAN INDONESIA 1 DI SMK NEGERI 3 KOTA SOLOK - Rahmawati, Nela; Baidar, Baidar; Yulastri, Asmar (Journal of Home Economics and Tourism, 2015)
The objective this research is to determine the relationship of the diciplinein the practical with the result of studen learning in subjects IndonesianFoodProcessing 1 at SMK N 3 Solok which covers aspects of diciline inpreparation of pratical, implemation pratical and result of the pratical. Thisresearch is correlation. The population in this study were all students of class XIculinary art SMK Negeri 3 Solok. The data analysis technique used is thecorrelation with product moment correlation formula. Based on the result of thedata analysis of the obtained result of research, learning diciline in praticaliscategories as good aspect and the result of the student learning are complete. Therelationship between the variable in the learning dicipline practies (X) with thelearning result tht Indonesian food processing 1 (Y) has a significant relationshipwith thitung > ttabel (3,721 > 2,048)Keyword: relationship of discipline in practical learning with the result study